Tsunami de béton : de l’empreinte à l’emprise sur les paysages littoraux après les catastrophes du 11 mars 2011 - Rémi Scoccimarro (Projets de Paysage)
On the eve of the Industrial Revolution, the coastal landscapes of Japan had already been highly anthropized. The arrival of Western technologies, including concrete, enabled an acceleration in the transformation of coastal landscapes. From the 1950s onwards, the Sanriku protective coastal works took the form of giant dikes on Japan’s tsunami coast. Disfiguring the inherited landscapes, these dikes also changed the relationship to the sea. During the tsunami of 11 March 2011, none of them resisted. But far from challenging this form of protection, post-tsunami reconstruction with its giant sea walls has increased the separation between the inhabitants and the sea. It has also made them even more dependent on the planners (state and regional authorities as well as construction and public works companies), whereas the potential for the appropriation of these structures remains unclear.